2021
DOI: 10.1111/ijfs.14974
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, thermal and structural properties of alkaline‐cooked (nixtamalised) chickpea (Cicer arietinum) flours

Abstract: The present study examined how the alkaline cooking process affects the chemical, thermal and structural properties of the chickpea, evaluating different lime concentrations. Cooking was carried out at 94°C, with two times of water for 15 min with five different lime concentrations. Regarding chemical composition, a decrease in protein and fat was observed: from 23.64% to a range of 18.26-19.93% for protein and from 8.20% to a range of 6.05-7.74% for fat. However, an increase was observed for ash and mineral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Mariscal‐Moreno et al . (2021) conducted a study to investigate the chemical, thermal and structural properties of alkaline‐cooked chickpea flours and found that formation of type 5 RS is possible in chickpeas. In a study conducted by Chávez‐Murillo et al .…”
Section: Resultsmentioning
confidence: 99%
“…Mariscal‐Moreno et al . (2021) conducted a study to investigate the chemical, thermal and structural properties of alkaline‐cooked chickpea flours and found that formation of type 5 RS is possible in chickpeas. In a study conducted by Chávez‐Murillo et al .…”
Section: Resultsmentioning
confidence: 99%